Cloud Computing untuk Pengelolaan Keuangan: Analisis Efisiensi dan Efektivitas - Dilla Salsabilla; Rosita Nur Awaliyah; Siti Nuraisyah; Afifah Nadiatul Muslihah; Oon Feriyanto (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The Fourth Industrial Revolution has brought fundamental transformations in various aspects of life, particularly in the business sector. Rapidly evolving technologies have triggered significant changes in payment systems, accounting, and financial management. One of the most notable innovations is the adoption of cloud computing technology. In the context of accounting efficiency, cloud computing offers significant benefits, including improved transaction processing speed, better record accuracy, and enhanced data analysis capabilities. However, data security remains a primary concern in the use of this technology. Threats such as data loss, data breaches, and cyberattacks require careful risk management. Practical recommendations such as data encryption and role-based access controls are needed to mitigate these risks. With careful management, cloud computing technology can become a driver of growth, innovation, and competitive advantage for companies in this digital era.